The influence of synthesis method on size and toxicity of CeO2 quantum dots: Potential in the environmental remediation. Issue 1 (January 2016) - Hassan, M. Shamshi; Khan, Rizwan; Amna, Touseef; Yang, Jiyeong; Lee, In-Hwan; Sun, Min-Young; EL-Newehy, Mohamed H.; Al-Deyab, Salem S.; Khil, Myung-Seob
Abstract: The present study reports the investigation of photocatalysis and bacterial toxicity of cerium oxide quantum dots (CeO2 QDs) synthesized by two different approaches. The 3 nm CeO2 QDs were synthesized by non-hydrolytic sol–gel method, while the 7 nm QDs were prepared by hydrothermal method. The samples prepared by the sol–gel method exhibited a red shift in the absorption spectrum. In the current study, we also report the influence of size of CeO2 QDs on the antibacterial activity and photocatalysis. The antibacterial study was performed by minimum inhibitory concentration (MIC) method using Escherichia coli as model organism. The MIC of CeO2 QDs was established to be 2.5 µg/mL and 5 µg/mL for 3 nm and 7 nm CeO2 QDs respectively. Further evaluation and interpretation of bacterial viability was done by means of dual fluorescent staining. The photocatalytic activity experiment indicated that 3 nm CeO2 QDs exhibited a higher photocatalytic activity for the photocatalytic decolonization of Rhodamine 6G aqueous solution under the visible-light illumination than 7 nm samples. The synthesized QDs are not only photocatalysts but are potent bactericides as well. Conclusively, the size dependent antimicrobial activity of CeO2 QDs was demonstrated for the first time in this report. The disruption of bacterial cell wall mechanism was found to be the probable mechanism responsible for bacterial toxicity. Thus, the reported CeO2 QDs are promising candidates for removal of chemical and biological pollutants and thus have great potential in the environmental remediation.